2016
DOI: 10.1021/acs.langmuir.6b00296
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of Doxorubicin and Selected Dyes on Carbon Nanotubes. Theoretical Investigation of Potential Application as a pH-Controlled Drug Delivery System

Abstract: This work shows results of a theoretical survey, based on molecular dynamics simulation, of potential applicability of doxorubicin coadsorption with various dyes molecules on/in carbon nanotubes as a drug delivery system. The central idea is to take advantage of the dyes charge distribution change upon switching the pH of the environment from neutral (physiological 7.4) to acidic one (∼5.5 which is typical for tumor tissues). This work discusses results obtained for four dye molecules revealing more or less in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…In addition to the chirality, the diameter and length of the nanotube affect the nanotube-H 2 interactions. The diameter changes cause the variation in the nanotube curvature affecting the arrangement of the molecular orbitals [4], and the nanotube length variation affects the diffusivity as was determined for drug adsorption [52]. E ph values decrease for nanotubes with a smaller diameter and a larger length (higher number of carbon-atom layers) but increase with the number of adsorbed H 2 .…”
Section: Hydrogen Adsorption For the Carbon Nanotubes With Defectsmentioning
confidence: 92%
“…In addition to the chirality, the diameter and length of the nanotube affect the nanotube-H 2 interactions. The diameter changes cause the variation in the nanotube curvature affecting the arrangement of the molecular orbitals [4], and the nanotube length variation affects the diffusivity as was determined for drug adsorption [52]. E ph values decrease for nanotubes with a smaller diameter and a larger length (higher number of carbon-atom layers) but increase with the number of adsorbed H 2 .…”
Section: Hydrogen Adsorption For the Carbon Nanotubes With Defectsmentioning
confidence: 92%
“…Panczyk et al has computationally shown that the chemotherapeutic drug doxorubicin (DOX) and several other hydrophobic dye molecules are readily adsorbed onto SWCNTs, and due to the protonation of the molecules at lower pH values, their release becomes favourable in low-pH environments that characterize tumor niches. 171 Exploiting this behaviour, Depan et al has shown that both DOX and folate-chitosan (a targeting molecule) can be loaded on GO sheets simply by mixing the two components with GO dispersed in aqueous solution. 172 DOX was released slowly in pH 5.3, but was retained in physiological pH 7.4.…”
Section: Drug Deliverymentioning
confidence: 99%
“…In addition, modeling of DOX interaction with some selected dyes (e.g., methyl red, neutral red, p-phenylenediamine and bromothymol blue) and carbon nanotubes has been described along with evaluation of the effect of lowered pH on drug release from such systems. The release of neutral red-DOX complex or free DOX from carbon nanotube surface was observed to occur after pH reduction [ 40 ]. However, to the best of our knowledge, there are no papers describing molecular dynamics study of the interactions between SRLS creating characteristic ribbon-like structures, taking CR as an example since it forms unique CR-DOX complexes with carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%